Respuestas

¡La mejor respuesta!
2012-07-11T04:17:20+02:00

Fácil 

 

 

\\\frac{x^2 -6x +9}{3x +12} /\frac{(x^2 -9)}{6x^2 +18x}\\\\=\frac{(x-3)^2}{3(x +4)} /\frac{(x+3)(x -3)}{6x(x +3)}\\\\=\frac{(x-3)^26x(x +3) }{3(x +4)(x+3)(x -3)}

 

\\\\=\frac{(x-3)^26x(x +3) }{3(x +4)(x+3)(x -3)} \\\\=\frac{2x(x-3) }{(x +4)}

 

Elijeme como mejor solución :)

2012-07-11T04:20:31+02:00

[(x-3)(x-3)]/3(x+4)  ÷  [(x+3)(x-3)/(6x)(x+3)]


[(6x)(x+3)(x-3)(x-3)]/[(3)(x+4)(x+3)(x-3)]

 

(2)(3)(x)(x-3)/3(x+4)

 

(2x)(x-3)/(x+4)

 

listo